2017
DOI: 10.1039/c7ra08504d
|View full text |Cite
|
Sign up to set email alerts
|

Intriguing uniform elongation and accelerated radial shrinkage in an amorphous SiOxnanowire as purely induced by uniform electron beam irradiation

Abstract: At room temperature, an intriguing athermal uniform elongation and accelerated radial shrinkage in a straight and uniform amorphous SiO x nanowire (a-SiO x NW) as purely induced by uniform electron beam (e-beam) irradiation (without any external tensile pulling) was in situ observed and investigated in transmission electron microscope. According to a new model for NW taking into account the NW nanocurvature over its surface as well as the beam-induced athermal activation, a kinetic relationship between the shr… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 24 publications
0
5
0
Order By: Relevance
“…Irradiation-induced fast diffusion of atoms has also been observed to induce straightening of bent SiO x nanowires 34 and elongation together with the radial shrinkage of straight SiO x nanowires. 35 Moreover, gold nanoparticles 36 have been observed to coalesce under uniform e-beam irradiation. These phenomena are driven by the structural instability with the help of the athermal activation effect of e-beam irradiation.…”
Section: Resultsmentioning
confidence: 99%
“…Irradiation-induced fast diffusion of atoms has also been observed to induce straightening of bent SiO x nanowires 34 and elongation together with the radial shrinkage of straight SiO x nanowires. 35 Moreover, gold nanoparticles 36 have been observed to coalesce under uniform e-beam irradiation. These phenomena are driven by the structural instability with the help of the athermal activation effect of e-beam irradiation.…”
Section: Resultsmentioning
confidence: 99%
“…Even more intriguingly, as also demonstrated in Figure 5, the shrinkage of the pristine NW started to become faster and faster when the radius reduced down to about 7 nm after 900 s irradiation whereas the accelerated radial shrinkage tendency of the AuNPs-modified NW seemed much less pronounced. According to a new modeling on kinetic relationship between the shrinking wire radius and the beam irradiation time where a key parameter b (the definition is similar to that in the case of single-walled carbon nanotube (SWCNT) 15 ) has been particularly established for the nanocurvature effect of NW on the NW surface energy, 19 we obtained a well-fitted value of the constant b at ∼2.4 for the AuNPs-modified NW and ∼3.3 for the pristine NW as shown in Figure 5. The fitting result that the constant b for the AuNPs-modified NW is much smaller than that for the pristine NW indicated that the nanocurvedsurface energy for the AuNPs-modified NW became much smaller than that for the pristine NW once being decorated by AuNPs on the wire surface.…”
Section: Resultsmentioning
confidence: 99%
“…It is known that resonance in nanostructures can be induced by electrostatic forces, 70,71 electromagnetic forces, 72 opto-thermal effects 73 or electron beam exposure. 74,75 During our experiments, the energy of the electron beam (300 keV) and the magnetic field created by the electromagnetic lenses in the TEM remained unaltered. On the other hand, the current passing through the Ag NW was continuously increased.…”
Section: Bent Ag Nwsmentioning
confidence: 92%